Qur'an and modern science conflict or conciliation ? - Islamic Research Foundation (Mumbai : Islamic Research Foundation [production company] ; Kuala Lumpur : SABA Islamic Media [distributor], 1996)
Some of the questions that have been answered in this videos are: Most religious scriptures do not conform with reason, logic and science. Isn't it ridiculous to ask if the Qur'an agrees or disagrees with modern science ; most scientist do not accept the existence of God, how can we accept God's Word as scientific ; can a scripture that describes the earth as a carpet be considered compatible with modern science
Copy available in DVD format
Copy available in DVD format
Speaker: Dr. Zakir Naik
Keywords: Qur'an and science